Explore a wide range of topics and get answers from experts on IDNLearn.com. Join our Q&A platform to access reliable and detailed answers from experts in various fields.
Sagot :
Answer:
A.
Step-by-step explanation:
x2 - 3x - 10. = 0
x2 + 2x - 5x - 10 = 0
(x2 + 2x) (-5x - 10) = 0
x (x + 2) - 5 (x + 2) = 0
(x - 5) (x + 2) = 0
x - 5 = 0 x + 2 = 0
x = 5 or x = - 2.
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Discover the answers you need at IDNLearn.com. Thanks for visiting, and come back soon for more valuable insights.